Avaliação das condições periodontais de diabéticos do tipo 2 com diferentes níveis glicêmicos - Costa, Katia Linhares Lima (2009)
Diabetes is a significant risk factor for the occurrence of periodontal diseases. Studying the relationship of both diseases in different populations with heterogeneous characteristics are still necessary to better understand them. The aim of this cross-sectional study was to evaluate the clinical periodontal parameters of type 2 diabetes patients with different levels of glycemic control. There were selected type 2 diabetics residing in the urban area of Sobral, Ceara. They must be non-smokers, aging 40 years or more and presenting at least and 6 teeth in their mouth. All had to be using any medication to control the glycemic level. Subjects were assigned to three groups based on their respective glycated hemoglobin levels - Hb1Ac (Control - C: Hb1Ac ≤ 7%, n=103; Moderate control - M: 7,1% ≤ Hb1Ac ≤ 9%, n= 60; Poor control = P: Hb1Ac ≥ 9,1%, n=22). The following clinical data were obtained from all patients: Plaque Index (PI), Gingival Index (GI), bleeding on probing (BOP), probing depth (PD) and gingival recession (GR). The mean age, number of teeth, PI, GI and BOP did not show any significance between groups. But this was observed for Hb1Ac mean levels and time of diabetes diagnosis. The presence of at least one periodontal site with PD ≥ 6 mm was considered for the diagnosis of periodontitis. There was no association between the increase of the glycemic level and the presence of periodontitis. However, data from patients presenting at least 20 teeth showed a significant association between periodontal diseases and higher glycemic levels. It can be concluded that the poor glycemic control was associated to the presence of periodontitis only in subjects with high number of teeth.